Triathletes and the development of disordered eating patterns - Valentine, S. (2001)
Female triathletes may be at higher risk for the development of disordered eating patterns. The cultural pressure to be thin, combined with the aesthetic and performance requirements of the sport may pressure the female triathlete to maintain a body weight that is unrealistic. These pressures can lead to pathogenic weight control practices as seen in anorexia nervosa, bulimia nervosa and disordered eating (anorexia athletica, obligatory exercise). Various risk factors have been suggested to be involved in predisposing an athlete to disordered eating and include; psychological factors, presence of dieting, specific exercise factors. It has been suggested that psychological factors present in high-level athletes, such as perfectionism and guilt, may increase the risk for an athlete to engage in disordered eating. The presence of dieting throughout the athletes lifetime may also predispose an athlete to disordered eating. Involvement in athletics may also perpetuate the disordered eating. For example, athletics may be used to legitimize an eating disorder. Athletes may be under the illusion that it is a good thing to restrict energy intake in order to perform better. Athletics can also be used as an excuse not to eat, which can set the scene for the next binge. Athletics can contribute to the downward spiral in weight by serving as a calorie burner. Excessive exercise, where exercise is essential and a top priority above other life goals, can contribute to the disordered eating cycle by serving as a way to purge. As a result of disordered eating, the female athlete may experience an increased risk for fractures, heart disease, osteoporosis, depression, and nutritional deficiencies. Education and screening for eating disorders need to be incorporated into triathlon coaching programs so that they can be prevented.